PENDEKATAN STRATEGI INSIDE-OUT DAN OUTSIDE-IN PADA PENDIRIAN BISNIS RINTISAN ENTREPRENEUR MUDA - Hendrik Rizqiawan; Iful Novianto; Andi Iswoyo; Yanuar Fauzuddin (Jurnal Riset Entrepreneurship, 2022)
The object of this study was a 25-year-old entrepreneur named Fahmi Fahrizal Pradianto. He was an employee affected by the covid-19 pandemic, which was eventually dismissed from work. But Fahmi did not give up, with the experience he had while working in a fast food restaurant, he opened a business that was also engaged in the same industry in Balongpanggang District of Gresik Regency, with spicy noodle products and various other processed under the Mie Rate brand. The business that was only started for 1 year turned out to be quite successful. Evidently, although still new, Fahmi has added branches in Lamongan Regency. This approach to research uses qualitative research methods, namely through the interview process to key informants, namely Fahmi as a business owner and 2 brothers who helped him run the Mie Rate. From this study it was found that indicators in inside-out strategies include experience, capital, parental support, self-image, and desire to growth. The indicators in the outside-in strategy are the existence of market opportunities and lack of competition, the availability of supporting information and communication technology media, and the availability of suppliers.